Understanding optics with python - Lakshminarayanan, Vasudevan; Ghalila, Hassen; Ammar, Ahmed; Varadharajan, L. Srinivasa (CRC series on multidisciplinary and applied optics, 2018)
"This book introduces optics through the use of simulations, namely, Python. Students, researchers, and engineers will be able to use Python simulations to better understand the basic concepts of optics and professors will be able to provide immediate visualizations of the complex ideas. Readers will learn programming in Python. Throughout this book, a simulated laboratory will be provided where students can learn by "hands on" exploration. The text will cover all the standard topics of traditional optics. "--Provided by publisher.